MiR-4454 in Combined Allergic Rhinitis and Asthma Syndrome (CARAS): Clinical significance and mechanistic insights into airway inflammation: miR-4454 in CARAS - Liu, Zhiguang; Sun, Chuang; Shi, Yujia; Wang, Zhipeng; Zhou, Lianzheng; Zhang, Qian; Mao, Zhengdao (Cellular and Molecular Biology, 2024)
Abnormal expression of non-coding microRNA is associated with the development of combined allergic rhinitis and asthma syndrome (CARAS). However, the function of miR-4454 in CARAS is unknown. Our study aimed to reveal the clinical significance and related mechanism of miR-4454 in CARAS. Blood samples from 38 cases of CARAS and 43 cases of healthy subjects were collected to detect the expression of miR-4454. House dust mite (HDM) sensitization and challenge-induced bronchial epithelial cells to simulate the asthma state model in vitro, miR-4454 mimics and inhibitor transfection to detect the expression level of pro-inflammatory cytokines, cell survival rate and migration ability, flow cytometry and western blot (WB) Detection of cell cycle, apoptosis and inflammation-related protein levels. Compared with healthy controls, the expression of miR-4454 in the blood of CARAS patients was significantly up-regulated, and IL-6 and IL-8 were significantly up-regulated in the HDM treatment group, indicating that the model induction was successful. After overexpression of miR-4454, cell proliferation and migration in the HDM-treated group were significantly inhibited, and the levels of early apoptosis and inflammation-related proteins (IL-17, IL-17RD, TNF-α, GCSF and NF-κB) were increased High; after inhibiting miR-4454, cell proliferation and migration were significantly enhanced, and the levels of apoptosis and inflammation-related proteins were decreased. This study found that inhibiting the expression of miR-4454 can improve HDM-induced cell injury, which may be related to miR-4454 regulating the activation of IL-17/NF-кB inflammatory axis.